Struktur Lapisan Bumi dalam Perspektif Hadis dan Sains - Wildan Firdaus; Sulalah Khairina; Khairul Muttaqin (El Nubuwwah Jurnal Studi Hadis, 2025)
The understanding of the Earthâ€™s layered structure has continued to develop within modern geological studies. Earth sciences describe the planet as consisting of several distinct layersâ€” the crust, mantle, outer core, and inner coreâ€”each with unique physical and chemical characteristics that play essential roles in geological dynamics such as plate tectonics, volcanism, and earthquakes. Meanwhile, Islamic tradition, through the hadiths of the Prophet Muhammad (peace be upon him), also contains indications of the Earthâ€™s layered nature, particularly in narrations mentioning the â€œseven layers of the Earth.â€ Although hadiths are not scientific texts, some scholars view these narrations as containing conceptual hints about the Earthâ€™s layered structure. This study aims to explore the concept of the Earthâ€™s layers from two perspectives: modern science and hadith studies. Using a qualitative-descriptive approach based on library research, this study examines relevant hadiths through a basic analysis of their chains of transmission and textual meaning, and compares them with contemporary geological literature. The findings reveal a conceptual intersection between the indications found in hadith and the scientific understanding of the Earthâ€™s structure, especially regarding the presence of vertically arranged layers. Ulama interpret the â€œseven Earthsâ€ in various waysâ€”some symbolically or spiritually, while others attempt to relate them to modern scientific divisions such as the lithosphere, asthenosphere, mesosphere, and the Earthâ€™s core layers.